Can Creatine Combat the Mental Fatigue-associated Decrease in Visuomotor Skills? - VAN Cutsem, Jeroen; Roelands, Bart; Pluym, Bert; Tassignon, Bruno; Verschueren, J O; DE Pauw, Kevin; Meeusen, Romain (Medicine and science in sports and exercise, 2020)
The importance of the brain in sports was recently confirmed by the negative effect of mental fatigue (MF) on sport-specific psychomotor skills. Creatine supplementation improves strength but can also improve cognitive functioning. To explore the role of creatine in combating MF, we evaluated whether creatine supplementation counteracts the MF-associated impairment in sport-specific psychomotor skills. In 23°C, 14 healthy participants (4 females, 10 males; mean ± SD, age = 24 ± 3 yr, mass = 74 ± 13 kg, height = 179 ± 9 cm) performed a 90-min mentally fatiguing task (counterbalanced, crossover, and double-blinded; i.e., Stroop task) in two different conditions: after a 7-d creatine supplementation (CR; 20 g·d) and after a 7-d calcium lactate supplementation (placebo [PLAC]), separated by a 5-wk washout. In both conditions, a 7-min sport-specific visuomotor task, a dynamic handgrip strength endurance task, and a 3-min Flanker task was performed before and after the mentally fatiguing task. Physiological and perceptual responses were measured throughout the protocol. Handgrip strength endurance was higher in CR compared with PLAC (P = 0.022). MF impaired visuomotor response time (+4.4%; P = 0.022) and Flanker accuracy (-5.0%; P = 0.009) in both conditions. Accuracy on the Stroop task was higher in CR compared with PLAC (+4.9%; P = 0.026). Within the perceptual and physiological parameters, only motivation and vigor (P ≤ 0.027) were lower in CR compared with PLAC. Creatine supplementation improved physical (strength endurance) and prolonged cognitive (Stroop accuracy) performance, yet it did not combat MF-induced impairments in short sport-specific psychomotor or cognitive (Flanker) performance. These results warrant further investigation in the potential role of creatine in combating the MF-associated decrements in prolonged (e.g., 90-min soccer game) sport performance and suggest a role of brain phosphocreatine in MF.